Convergence of Antiperiodic Boundary Value Problems for First-Order Integro-Differential Equations - Yameng Wang; Juan Zhang; Yufeng Sun (Discrete Dynamics in Nature and Society, 2020)
In this paper, we investigate the convergence of approximate solutions for a class of first-order integro-differential equations with antiperiodic boundary value conditions. By introducing the definitions of the coupled lower and upper solutions which are different from the former ones and establishing some new comparison principles, the results of the existence and uniqueness of solutions of the problem are given. Finally, we obtain the uniform and rapid convergence of the iterative sequences of approximate solutions via the coupled lower and upper solutions and quasilinearization method. In addition, an example is given to illustrate the feasibility of the method.